2013
DOI: 10.1371/journal.pone.0076893
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of oxLDL and IL-10 Production by Macrophages Requires PAFR and CD36 Recruitment into the Same Lipid Rafts

Abstract: Macrophage interaction with oxidized low-density lipoprotein (oxLDL) leads to its differentiation into foam cells and cytokine production, contributing to atherosclerosis development. In a previous study, we showed that CD36 and the receptor for platelet-activating factor (PAFR) are required for oxLDL to activate gene transcription for cytokines and CD36. Here, we investigated the localization and physical interaction of CD36 and PAFR in macrophages stimulated with oxLDL. We found that blocking CD36 or PAFR de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 43 publications
(57 reference statements)
1
37
0
4
Order By: Relevance
“…This axis activates expression of Th17 cell cytokines, such as IL17, IL23, or IL6 and synergizes with CD36 to enhance the IL10 secretion in macrophages (47,48). Considering that immune cells in cancer microenvironment have important functions in cancer progression through producing many cytokines (49,50), the PAF/PAFR axis in cancer microenvironment, may also influence cancer growth and metastasis via regulating cytokine secretion in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…This axis activates expression of Th17 cell cytokines, such as IL17, IL23, or IL6 and synergizes with CD36 to enhance the IL10 secretion in macrophages (47,48). Considering that immune cells in cancer microenvironment have important functions in cancer progression through producing many cytokines (49,50), the PAF/PAFR axis in cancer microenvironment, may also influence cancer growth and metastasis via regulating cytokine secretion in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…16 By contrast, the blockage of CD36 reduced the secretion of IL-1β, IL-6 and IL-8 and foam cell formation in human macrophages. 17 Based on the results of the above studies, it can be concluded that reduction of CD36 receptor expression on macrophages prevents the development of atherosclerosis.…”
Section: Plateletsmentioning
confidence: 95%
“…Rios et al showed that blocking CD36 and PAFR (Platelet Activating Factor) decreases oxLDL uptake and IL-10 production by macrophages as well as PAFR and CD36 are colocalized in human atherosclerotic plaques. 16 They found that uptake of oxLDL and IL-10 production induced by oxLDL increasing the phosphorylation of PPARγ. This results in reduced transcription of CD36 mRNA.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophages have high expression of F4/80, CD36, and TLRs, whereas DCs present high expression of MHCII, costimulatory molecules (CD80, CD86, CD40), TLRs, and have properties of antigen presenting cells higher than macrophages. We showed before that CD36 is a scavenger receptor able to assemble with PAFR in lipid rafts to interact with PAFR ligands and enhance the production of IL-10 by macrophages [17,31]. These effects were abrogated in the presence of PAFR antagonists or anti-CD36 blocking antibody [17].…”
Section: Discussionmentioning
confidence: 97%